Palopegteriparatide (Yorvipath) - CDA-AMC (Canadian Journal of Health Technologies, 2026)
Canada’s Drug Agency (CDA-AMC) recommends that Yorvipath be reimbursed by public drug plans for the treatment of adults with chronic hypoparathyroidism that is not adequately controlled with conventional therapy (calcium and calcitriol) if certain conditions are met. The Canadian Drug Expert Committee (CDEC) determined that it is uncertain whether Yorvipath demonstrates acceptable clinical value versus conventional therapy in patients with chronic hypoparathyroidism that is not adequately controlled with conventional therapy. Yorvipath may be used as an alternative to conventional therapy over time; however, given that Yorvipath is expected to be initiated as an additive treatment to conventional therapy, acceptable clinical value refers to added value versus conventional therapy. Evidence from a clinical trial showed that treatment with Yorvipath for 26 weeks increased the proportion of patients with chronic hypoparathyroidism not adequately controlled by conventional therapy who had a treatment response, defined as normal calcium levels in the blood and independence from conventional therapy, compared with conventional therapy. This result was consistent with findings in the overall trial population with chronic hypoparathyroidism. Long-term evidence up to week 182 suggests that the treatment effect was maintained over time. The potential long-term renal benefit with Yorvipath remains uncertain, as the design and duration of the clinical trial were not sufficient to evaluate this outcome. Conventional therapy does not target the underlying cause of hypoparathyroidism. Many patients have difficulty managing the symptoms of hypoparathyroidism, are unable to maintain normal calcium and phosphorous levels in the blood, and are at risk of long-term complications of hypoparathyroidism. Based on all of the preceding considerations, CDEC concluded that treatment with Yorvipath may address a significant unmet clinical need to a degree that justifies a positive recommendation despite uncertainty about its clinical value. Yorvipath should only be covered for adult patients diagnosed with chronic hypoparathyroidism that is not adequately controlled by conventional therapy, defined as meeting at least 1 of the following criteria while receiving optimized hypoparathyroidism-related supplements: low calcium levels in the blood with symptoms, high phosphate levels in the blood, reduced kidney function, high calcium levels in the urine, and intolerance to high doses of, or requiring high doses of, conventional therapy. Yorvipath should only be reimbursed if the cost of Yorvipath is reduced, and if the patient’s condition shows a treatment response (i.e., meets all of the following criteria: normal calcium levels in the blood, independence from active vitamin D, and at least a 50% reduction in the dose of therapeutic calcium). A response to treatment should be assessed after the initial authorization period of 26 weeks, and reassessed at least every 12 months thereafter. Yorvipath should be prescribed and monitored by health care professionals with experience in the diagnosis and management of patients with hypoparathyroidism. Important budget impact considerations must be addressed for health systems to be able to adopt Yorvipath.